Experimental investigation on emissivity of 75Ni-25Cr alloy coated Aluminium surface for the purpose of solar applications. (2021) - Sivakumar, K.; Rajendra Prasad, A.; Jagadesh, T.; Dinesh Kumar, S.; Ponshanmugakumar, A.; Thamilarasan, K.
Abstract: Aluminium is easily available low cost material but the emissivity of the aluminium is very low which is minimum 0.02 to maximum 0.54 for the pure level with different form like polished, highly polished, oxidized, un-oxidized and anodized conditions and different formations. So in this investigation focused to increase the emissivity of the Aluminium surface. There are number of methods and materials were available to reach the motive of this requirement among them coating method and 75Ni-25Cr alloy material considered for this experimental investigation. Square plates were considered and the corresponding temperatures measured with the help of thermocouples located on the particular point of the surface. The commonly used normal black body used as a reference surface for this investigation. There are increased radiant heat input create impact on the values surface which leads to identify the purpose of this material coating.